A New Design of a CPW-Fed Dual-Band Monopole Antenna for RFID Readers - Ahmed El Hamraoui; EL Hassane Abdelmounim; Jamal Zbitou; Hamid Bennis; Mohamed Latrach (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper comes with a new dual-band planar monopole antenna fed by Coplanar Waveguide (CPW) line designed for RFID readers and it operates at 2.45 GHz, 5.80 GHz. This antenna is designed with reasonable gain, low profile and low cost production. The designed antenna based on theoretical equations is simulated and validated by using ADS from Agilent technologies and CST Microwave Studio electromagnetic solvers. A parametric study of the proposed antenna has been carried out by optimizing some critical parameters. The antenna has a total area of 35×38 mm2 and mounted on an FR4 substrate with dielectric permittivity constant 4.4 and thickness of 1.6 mm and loss tangent 0.025. The comparison between simulation and measurement results permits to validate the final achieved antenna structure in the desired RFID frequencies bands. Details of the proposed antenna design and both simulated and experimental results are described and discussed